Tourism for All: Digital Solutions for Improving Accessibility in Tourism - Denizova, Veronika (Research Papers, 2025)
Innovative technologies provide persons with disabilities greater opportunities to plan, book and participate in travel activities. This publication presents technological and digital solutions that support accessible tourism. It highlights the importance of technology as a critical element of improving destination accessibility and provides insights into successful practices in facilitating access to tourism activities for persons with disabilities. Particular attention is paid to mobile applications, online platforms, artificial intelligence (AI), Virtual and Augmented reality (VR and AR) and the Internet of Things (IoT), which provide personalized and accessible solutions for tourists with different needs. It is stated that an integrated approach including digital innovation, physical infrastructure and active user feedback is needed to achieve effective accessibility. A more inclusive and accessible tourism sector for all can be achieved through targeted investment and collaboration. Based on the analysed case studies and successful examples, conclusions and recommendations are drawn for tourism businesses and destinations for integrating technological innovations in improving accessibility.